Indic Science of Consciousness: Chronological Relevance to the Indic Knowledge Traditions and Modern Science - S Rukmini (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2020)
In the recent years there seems to be a renaissance of Indic knowledge traditions and this is quite evident from the growing interest among the modern researchers and scholars to unearth the great insights and knowledge that made ancient Indian civilization one of the unique in the world. India as a nation of rich spiritual heritage and diverse knowledge systems have become the most sort out nation across the globe in terms of wisdom and insights on the philosophy of mind and consciousness. Further, research findings in different fields of knowledge such as consciousness studies, health and healing, psychology and mental health, mathematics, physics, astronomy, economics, law and governance, archaeology and history are in good agreement and deeply correlated with the information inscribed in the ancient Indian scriptures. Ancient Indians deeply engrossed in understanding the ontological and epistemological basis of knowledge advocated Vedas as the ultimate source of knowledge. Vedas are considered as the oldest repository of spiritual knowledge in the world, where the prime emphasis is on understanding the nature of mind and consciousness, as this forms the fundamental basis to Indic knowledge. So, here, we propose that the science of consciousness seems to be the first and foremost in the chronology in the world of knowledge. An intuitive and analytical framework that resulted from a deeper understanding of the nature of mind and consciousness paved the way for the development of different Indic knowledge systems. Inner insight emerged through this approach is embraced to understand the external world and formulate different theories and principles of Indic knowledge. From a chronological perspective, Indian science and wisdom emerged in the later stages of development of the science of consciousness. So, the aim of the present paper is to throw light on the Indic science of consciousness and examine chronology of the emergence of other fields of Indic knowledge.